PENGUKURAN KEPUASAN PENGGUNA LAYANAN WEBSITE E-LEARNING UNIVERSITAS BINA DARMA PALEMBANG - Patricia Aprilla Quiroz; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
The rapid development of IT has made the website an integral part of an educational institution in terms of services for the academic community, lecturers, students and education staff. The service of a web-based academic information system needs to be measured to determine the level of user satisfaction. In this study, the quality of the university's academic system website was measured using the WebQual 4.0 method, while the data used was quantitative data. From the research results it can be concluded that only one WebQual 4.0 variable, namely Service Interaction Quality has a significant effect on User satisfaction (user satisfaction) on the university's academic system website.